COMMUNICATIVE COMPETENCE OF FILIPINO ENGLISH LANGUAGE TEACHERS: BASIS FOR A DEVELOPMENT PROGRAM - Esgrina, Francisco Jr. Olermo (LLT Journal: A Journal on Language and Language Teaching, 2024)
Ongoing professional development and implementation of supportive educational policies are important to address the linguistic challenges faced by non-native English language teachers (NNETs). These would enhance educational outcomes for students and improve the quality of basic education. This mixed-method exploration of the communicative competence of NNETs in Arakan, North Cotabato, Philippines, used descriptive-evaluative design, correlation, and In-Depth Interviews (IDIs). The findings showed that predominantly young female NNETs with diverse educational backgrounds had significant deficiencies in phonology and notable inadequacies in syntax, morphology, lexicon, and orthography despite their diligence in lesson preparation. Significant correlations were found between the subjects taught and lexicon proficiency, as well as the number and types of subjects handled and morphology competence. However, no significant correlations existed between their competence and educational attainment, job description, or seminar attendance. Additionally, significant differences were observed in orthographic proficiency by age and syntactic proficiency by gender, while civil status did not significantly impact competence levels. These findings underscore the urgent need for targeted professional development for NNETs. Specialized training or advanced English courses are essential to address linguistic shortcomings. With improved grammatical and linguistic skills, NNETs can enhance their pedagogical effectiveness and ensure the delivery of quality basic education.